EXPOSING MODERN DISCRIMINATION: REFLECTING ON STRUGGLES OF THE AFRICAN-AMERICAN DEPICTED IN JUDAS AND THE BLACK MESSIAH - Fikzia, Iffah; Saktiningrum, Nur (Pengkajian Amerika, Universitas Gadjah Mada, 2024)
The passage of the Civil Rights Act of 1964 is expected to reduce the injustices faced by African Americans. However, life after the Act proves to be not easy. The issues of oppression experienced by African Americans in the past continue to recur. This is because some discrimination against black people is done in a more latent way, called modern discrimination. Therefore, it is important to discuss modern discrimination against African Americans as depicted in Judas and the Black Messiah movie This article aims to analyze the causes of modern discrimination against African Americans. In this research, the researcher used a qualitative method through library research. The main data was taken from the dialogue of Judas and the Black Messiah movie, while supporting data came from articles, books, and online sources. The researcher applied a post-nationalist perspective, Critical Race Theory, and modern discrimination theory. The research findings identify four key factors explaining modern discrimination against African Americans: normalization of discrimination, exploitation of minority interests to support white dominance, adaptation of African-American stereotypes to fit white demands, and the intersectionality of multiple sources contributing to discrimination.